Inter-state burden cost model and their management for waqf financing of higher education - Shamsudin, Ahmad Faizul; Abidin, Izham Zainal; Hashim, Jamil; Wan Yusof, Wan Sabri; Yusof, Anas; Hashim, Hanita (Al-Qimah Al-Mudhafah, 2022)
This paper is about the costing of burdens (e.g., environmental degradation) and its management for inter-State Waqf flows in utilizing the natural resources in Malaysia. The purpose is to have greater accountability in the management of Waqf funds across State boundaries to finance higher education. The problem is to determine the cost models of these burdens that may affect the costs of Waqf transfer between the states concerned. In addition these costs are divided by the different sources of the revenue from which Waqf has been allocated. A costing algorithm is developed to build the cost model using Bailek’s power tracing technique in the Power World Binary Simulator (PWS). The results indicate that the hourly costs of burdens increase as the number of states participate in the inter-state waqaf flows. This may imply that less participating States may improve the management of Waqf fund flows across the states.